Cloud platform to improve efficiency and coverage of asynchronous multidisciplinary team meetings for patients with digestive tract cancer - Zhang, Yu; Li, Jie; Liao, Min; Yang, Yalan; He, Gang; Zhou, Zuhong; Feng, Gang; Gao, Feng; Liu, Lihua; Xue, Xiaojing; Liu, Zhongli; Wang, Xiaoyan; et al. (Frontiers in Oncology, 2024)
Background: Multidisciplinary team (MDT) meetings are the gold standard of cancer treatment.However, the limited participation of multiple medical experts and the low frequency of MDT meetings reduce the efficiency and coverage rate of MDTs. Herein, we retrospectively report the results of an asynchronousmodified MDT based on a cloud platform (cMDT) to improve MDT meetings' the efficiency and coverage rate of MDT meetings for digestive tract cancer.The participantsparticipating members and cMDT processes associated withfor digestive tract cancer were discussed using a cloud platform. Software programming and cMDT test runs were subsequentlythen conducted to further improve the software and processingprocesses. cMDT for digestive tract cancer was officially launched in June 2019. The doctor response durationtime, cMDT time, MDT coverage rate, the National Comprehensive Cancer Network guidelines compliance rate for patients with stage III rectal cancer, and uniformity rate of medical experts' opinions were collected.The final cMDT software and processes used were determined. Among the 7462 digestive tract cancer patients, 3143 (control group) were diagnosed between March 2016 and February 2019, and 4319 (cMDT group) were diagnosed between June 2019 and May 2022. The average number of doctors participating in each cMDT was 3.26±0.88. The average doctor response time was 27.21±20.40 hoursh, and the average durationtime of cMDT was 7.68±1.47 min.The coverage rates were 47.85% (1504/3143) and 79.99% (3455/4319) in the control and cMDT groups, respectively. The National Comprehensive Cancer Network guidelines compliance rates for stage III rectal cancer patients were 68.42% and 90.55% in the control and cMDT groups, respectively. The uniformity rate of medical experts' opinions was 89.75% (3101/3455), and 8.97% (310/3455) of patients needed online discussion through WeChat; only 1.28% (44/3455) of patients needed face-to-face discussion with the cMDT group members. Conclusions: A cMDT can increase the coverage rate of MDTs and the compliance rate with National Comprehensive Cancer Network guidelines for stage III rectal cancer. The uniformity rate of the medical experts' opinions was high in the cMDT group, and it reduced contact between medical experts during the COVID-19 pandemic.